2022
DOI: 10.1021/acsaem.2c02171
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Preparation of Flexible and Green Cellulose-Based Electrothermal Composites for Joule Heating Applications

Abstract: Cellulose-based electrothermal composites (CETCs) are a type of functional material that combines a cellulose substrate with a heat generator to form multifunctional electrothermal composites with outstanding mechanical properties, biodegradability, flexibility, and Joule heating performance. The forms of cellulose include nanocellulose, cellulose fibers, cellulose paper, and cellulose fabrics. The heat generators include carbon-based materials (e.g., graphene and carbon nanotubes), metal nanowires, metal carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 126 publications
(177 reference statements)
0
9
0
Order By: Relevance
“…Cellulose Nanomaterials CNC, CNFs, BC [56] Cellulose Derivatives Cellulose ethers (carboxymethyl cellulose (CMC), ethyl cellulose), cellulose esters (cellulose acetate), Cellulose Nitrate, Cellulose Sulfate, Methyl Cellulose [41] Commercial Cellulose Products Cellulosic Fabric, Cellulosic Yarn [57] cellulose, where cellulose acted as the tough component and graphene oxide (GO)/MXene acted as the conductive component. [60] The prepared MXene-based fiber exhibited a tensile strength of 134.7 MPa, a large elongation at break of 13 %, and a high conductivity of 2.37×10 3 S/m.…”
Section: Cellulosic Materialsmentioning
confidence: 99%
“…Cellulose Nanomaterials CNC, CNFs, BC [56] Cellulose Derivatives Cellulose ethers (carboxymethyl cellulose (CMC), ethyl cellulose), cellulose esters (cellulose acetate), Cellulose Nitrate, Cellulose Sulfate, Methyl Cellulose [41] Commercial Cellulose Products Cellulosic Fabric, Cellulosic Yarn [57] cellulose, where cellulose acted as the tough component and graphene oxide (GO)/MXene acted as the conductive component. [60] The prepared MXene-based fiber exhibited a tensile strength of 134.7 MPa, a large elongation at break of 13 %, and a high conductivity of 2.37×10 3 S/m.…”
Section: Cellulosic Materialsmentioning
confidence: 99%
“…11 Therefore, research into thermally conductive polymer-based composites have been fueled by the requirement for flexible conductive materials with good heat dissipation and lower thermal expansion. 13 Composite electrothermal heaters are prepared by addition of electrothermally conductive fillers to the polymer matrix, and the internal fillers produce heat when a voltage is applied. 14 Due to the higher λ value, lower thermal expansion and high corrosion resistance, carbon-based fillers such as carbon black (CB), graphite, graphene, and carbon nanotubes (CNT) are ideal for composite electrothermal heaters, and CB is often used because of its relative cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Composite electrothermal heaters are prepared by addition of electrothermally conductive fillers to the polymer matrix, and the internal fillers produce heat when a voltage is applied . Due to the higher λ value, lower thermal expansion and high corrosion resistance, carbon-based fillers such as carbon black (CB), graphite, graphene, and carbon nanotubes (CNT) are ideal for composite electrothermal heaters, and CB is often used because of its relative cost effectiveness. , Many studies have reported electrothermal composites developed using different polymer matrices, for example, thermoplastic polyurethane, polyimide, silicone elastomers, and cellulose, combined with carbon based fillers. ,,, Previous composite film heater prototypes have exhibited impressive success, yet require more improvements in thermal cycling, cost-efficiency, and stability to allow for translation to industrial applications .…”
Section: Introductionmentioning
confidence: 99%
“…Smart textile materials with high-performance and multifunctional environmentally friendly features are highly demanded owing to the rapid developments of the industry and living standards. , The developments and innovations of the textile industry mainly focus on durability, intelligence, functionality, and sustainability. , Multifunctional finishing can endow the textiles with additional performances including fluorescence, antibacterial activity, electrical conductivity, hydrophobicity, oil repellency, and so on, which have shown significant application prospects in different industrial and civil yields. Cotton fabric-based functional textiles are highly popular among those different kinds of fabrics due to their high stability, skin affinity, biodegradability, and high strength. Special attention has been devoted to some fascinating fields of cotton textile research like water-proof textiles, medical textiles, and antifouling textiles by using innovative chemical agents or finishing methods. , Despite all this, the hydrophilicity induced by polyhydroxyl groups in the cellulose skeleton has hindered the application of cotton-based materials in some technical fields with special needs like transport systems and resource recovery. …”
Section: Introductionmentioning
confidence: 99%
“…Special attention has been devoted to some fascinating fields of cotton textile research like water-proof textiles, medical textiles, and antifouling textiles by using innovative chemical agents or finishing methods. 9,10 Despite all this, the hydrophilicity induced by polyhydroxyl groups in the cellulose skeleton has hindered the application of cotton-based materials in some technical fields with special needs like transport systems and resource recovery. 11−13 The functional finishings of cotton fabrics are usually achieved using the coating method or surface grafting, and hydrophobic cotton fabrics are usually obtained by coating organic polymers or inorganic nanomaterials, such as organosilicon, polystyrene, TiO 2 , and so on.…”
Section: ■ Introductionmentioning
confidence: 99%